Students’ self-compassion and academic resilience in pandemic era - Yustika, Yustika; Widyasari, Pratiwi (Universitas Negeri Padang, 2021)
During the covid-19 pandemic, 12th grade high school students felt more stressed and tired due to a continued isolation. Therefore, academic resilience is needed so that students can face existing academic problems. It was found that self-compassion can foster resilience. This study aims to analyze the relationship between self-compassion using the Indonesian version of the Self-Compassion Scale and Academic Resilience using the Academic Resilience Scale-30. 277 participants from 12th grade high school students who are distance learning took part in this correlational research. Results show that there is a positive correlation between self-compassion and academic resilience. This therefore results in a new finding of how students could be more academically resilient in facing academic burdens during the pandemic. To get a more comprehensive picture, future studies could explore more demographic data, such as whether anyone assists students while distance learning and how stressed students are.